2016
DOI: 10.1007/s10551-016-3048-3
|View full text |Cite
|
Sign up to set email alerts
|

Truthfulness in Accounting: How to Discriminate Accounting Manipulators from Non-manipulators

Abstract: Preparers of accounting information are in a position to manipulate the view of economic reality presented in this information to interested parties. These manipulations can be regarded as morally reprehensible because they are not fair to users, they involve an unjust exercise of power, and they tend to weaken the authority of accounting regulators. This paper develops a model for detecting earning manipulators using financial statements ratios in a sample of Spanish listed companies. Our results provide evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 100 publications
0
35
0
2
Order By: Relevance
“…Vladu et al (2016) develop a model for detecting earnings manipulators using financial statement ratios from a sample of Spanish listed companies. They suggest that their proposal can be extremely useful in detecting manipulators and can be employed by a wide range of users of accounting information including stock exchange supervisors or investment professionals.…”
Section: Misbehaviors In Accounting and Financementioning
confidence: 99%
“…Vladu et al (2016) develop a model for detecting earnings manipulators using financial statement ratios from a sample of Spanish listed companies. They suggest that their proposal can be extremely useful in detecting manipulators and can be employed by a wide range of users of accounting information including stock exchange supervisors or investment professionals.…”
Section: Misbehaviors In Accounting and Financementioning
confidence: 99%
“…Some researchers note that certain earnings management behaviour is acceptable under conventional accounting standards (Bruns & Merchant, 1990;Merchant & Rockness, 1994;Parfet, 2000;Arya, Glover, & Sunder, 2003). Other scholars regard earnings management behaviour as going against the value of religion (Ronen & Yaari, 2008;Loomis, 1999;Grant, DePree Jr, & Grant, 2000;Solomon, 1992;Rawls, 1972;Vladu, Amat, & Cuzdriorean, 2017;Farrell, 2015;Abdullah et al, 2014). For instance, earnings management behaviour goes against the truthfulness of accounting (Ronen & Yaari, 2008); it is intolerable (Loomis, 1999;Grant et al, 2000); it is immoral (Solomon, 1992) and it goes against the principle of justice (Rawls, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, earnings management behaviour goes against the truthfulness of accounting (Ronen & Yaari, 2008); it is intolerable (Loomis, 1999;Grant et al, 2000); it is immoral (Solomon, 1992) and it goes against the principle of justice (Rawls, 1972). The financial losses witnessed in Enron, WorldCom, Tyco International (Vladu et al, 2017), Olympus, Tesco (Farrell, 2015) and Satyam Computer Services (U.S. Securities and Exchange Commission (SEC), 2011) within the international front and Transmile and Megan Media in Malaysia (Abdullah et al, 2014) have all been linked, whether directly or indirectly, to issues of deception, misleading information and untruthful accounting.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, among the latest studies aimed at investigating the use of discretion by managers and the possible phenomena of earnings management, there is the study by Dechow et al (2012). Based on these experiences, Vladu et al (2017) have identified a series of financial statement ratios that can enable the identification of any EM phenomena by managers (or, in general, by those who are able to use their dominant position in order to adapt the budget results to their own personal purposes). This model, although paving the way for new research questions, seems more aimed at a statistical identification of the elements particularly subject to EM practices in the financial statement.…”
Section: Identification Of Evaluative Discretion and Earnings Managemmentioning
confidence: 99%